2020
DOI: 10.1002/sstr.202000052
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrrole‐Fused Asymmetrical Electron Acceptor for Polymer Solar Cells with Approaching 16% Efficiency

Abstract: Selecting suitable aromatic rings to develop asymmetric small‐molecule acceptors (SMAs) is of great significance. Herein, two asymmetric SMAs, namely, BTN‐4F and BTSe‐4F, are successfully synthesized by incorporating pyrrole and selenophene unit into the cores, respectively. Compared with the selenophene‐fused counterpart BTSe‐4F, BTN‐4F displays slightly upshifted energy levels and red‐shifted absorption spectrum (about 40 nm in film) due to the strong electron‐donating ability of N atoms in pyrrole. When mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…As a result, the PM6:BTN-4F OSCs obtained a PCE of 15.82%, with a V OC of 0.82 V, a J SC of 25.05 mA cm -2 , and a FF of 77.3%, higher than that (13.79%) of the PM6:BTSe-4F device. [88] Lately, Yang et al reported two asymmetric FREAs with A-DA 1 D'-A structure, namely C-shaped BDTP-4F and S-shaped BTDTP-4F. [89] The maximum extinction coefficient (ε max ) of BTDTP-4F was 2.61 × 10 5 m −1 cm −1 at 761 nm, higher than that of BDTP-4F (2.40 × 10 5 m −1 cm −1 at 750 nm) in chloroform solution.…”
Section: The Asymmetric Central Core-based Freasmentioning
confidence: 99%
“…As a result, the PM6:BTN-4F OSCs obtained a PCE of 15.82%, with a V OC of 0.82 V, a J SC of 25.05 mA cm -2 , and a FF of 77.3%, higher than that (13.79%) of the PM6:BTSe-4F device. [88] Lately, Yang et al reported two asymmetric FREAs with A-DA 1 D'-A structure, namely C-shaped BDTP-4F and S-shaped BTDTP-4F. [89] The maximum extinction coefficient (ε max ) of BTDTP-4F was 2.61 × 10 5 m −1 cm −1 at 761 nm, higher than that of BDTP-4F (2.40 × 10 5 m −1 cm −1 at 750 nm) in chloroform solution.…”
Section: The Asymmetric Central Core-based Freasmentioning
confidence: 99%
“…Commonly used outermost aromatic rings in A–D–A-type SMAs include thiophene, selenophene, thieno[3,2- b ]thiophene, thieno[3,2- b ]selenophene [ 27–30 ], dithieno[3 , 2- b : 2 ′ , 3 ′ - d ]thiophene [ 31–33 ] and dithieno[3 , 2- b : 2 ′ , 3 ′ -d]pyrrole (DTP) [ 34–36 ]. In comparison with thiophene and selenophene, pyrrole is the most electron-rich five-membered single aromatic ring, which can enhance the ICT effect, reduce optical band gaps ( E g opt ) and increase the energy level of the LUMO of SMAs [ 37–39 ]. Additionally, fine-tuning the side chains on pyrrole can improve the molecular packing, the solubility and the mobility of SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] In recent years, a number of nonfullerene small-molecule acceptors (SMAs) have been exploited to remedy the drawbacks of fullerene acceptors. [16][17][18][19][20] Among the different types of SMAs, the most popular SMAs consist of acceptor-donor-acceptor (A-D-A) architecture, which produces most of the devices with top-of-the-line efficiencies and low energy losses. [21][22][23][24][25][26][27][28][29][30] The evolution of SMAs in the past five years mainly aims to improve the physical and chemical properties of the molecules, including the absorption spectra, energy levels, and molecular packing behaviors.…”
Section: Introductionmentioning
confidence: 99%